The Effectiveness of Cooperative Learning Model of the TSTS Type Observed From the Interpersonal Intelligence Toward the Mathematical Competency - Agustika, G.N. Sastra; Yusi Lestari, Ni Md.; Wiarta, I Wyn. (LPPM Undiksha, 2019)
This study aimed to find out the effectiveness of cooperative learning model of the Two Stay Two Stray type observed from interpersonal intelligence toward Mathematical competency on the fourth grade at SDN Moh. Hatta. This study was a quasi-experimental design with 2 x 2 factorial design. The population of this study were 244 students on the fourth grade of SDN Moh. Hatta in academic year of 2018/2019. The selection of the control group and the experimental group was conducted randomly. The data were collected using test and non-test methods. The data were analysed using 2-lane variance analysis. Based on the results of 2-lane variance analysis, it is obtained that (1) FA = 10,606 > F tabel (? = 0,05; 1;75)) = 3,969. Therefore, the null hypothesis (H0) is rejected. It signifies that ?there is a significant difference in Mathematical competency between group of students who are taught through cooperative learning model of Two Stay Two Stray type and group of students who are taught using conventional learning?, (2) FB = 0,201 < F tabel (? = 0,05; 1;75))= 3,969. Therefore, the null hypothesis (H0) is accepted. It means that ?there is no significant difference in Mathematical competency between students who have high interpersonal intelligence and students who have low interpersonal intelligence on Mathematical competency?, (3) FAB = 0,502 < F tabel (? = 0,05; 1;75))= 3,969. From the last results, the null hypothesis (H0) is accepted. It means that ?there is no significant interaction between cooperative learning model of Two Stay Two Stray type and interpersonal intelligence on Mathematical competency. The results of the treatment effectiveness calculation obtained the score of n2 = 0,122 . Overall, it can be concluded that the application of the learning model has an influence on the Mathematical competency by 12,2%.